2015
DOI: 10.1111/jpi.12205
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin sensitizes human breast cancer cells to ionizing radiation by downregulating proteins involved in double‐strand DNA break repair

Abstract: Radiation and adjuvant endocrine therapy are nowadays considered a standard treatment option after surgery in breast cancer. Melatonin exerts oncostatic actions on human breast cancer cells. In the current study, we investigated the effects of a combination of radiotherapy and melatonin on human breast cancer cells. Melatonin (1 mm, 10 μm and 1 nm) significantly inhibited the proliferation of MCF-7 cells. Radiation alone inhibited the MCF-7 cell proliferation in a dose-dependent manner. Pretreatment of breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 59 publications
4
53
1
Order By: Relevance
“…The second reason is the difference in the administration time. In a previous study , incubation with melatonin (1 m m , 10 μ m , and 1 n m ) significantly inhibited the proliferation of human breast cancer cells at 3 and 6 days; however, in the current study, the experimental cycle was only 2 days. The final reason is the difference in signaling pathways.…”
Section: Discussioncontrasting
confidence: 80%
“…The second reason is the difference in the administration time. In a previous study , incubation with melatonin (1 m m , 10 μ m , and 1 n m ) significantly inhibited the proliferation of human breast cancer cells at 3 and 6 days; however, in the current study, the experimental cycle was only 2 days. The final reason is the difference in signaling pathways.…”
Section: Discussioncontrasting
confidence: 80%
“…Using culture‐activated primary rat HSC, we show in this study that melatonin suppresses HSC proliferation and activation directly. The antiproliferative action of melatonin has been intensively studied for cancer cells, in particular that of the colon , liver , breast , ovary , prostate , and pancreas . There is no universal mechanism that controls the oncostatic function of melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that breast cancer patient with RAD51, a key player in homologous recombination and DNA repair system overexpression are more prone to resist against radiotherapy. Noteworthy, it was observed that melatonin administration for these subset of patients sensitized them to radiotherapy by downregulation of RAD51 [79].…”
Section: The Concomitant Use Of Melatonin and Chemotherapeutic Agentsmentioning
confidence: 95%